2020
DOI: 10.1186/s12877-020-01620-w
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function of older adults engaging in physical activity

Abstract: Background: Physical activity can be classified as open-skilled or closed-skilled. Open-skilled physical activity, such as tennis, require participants to perform within a dynamic setting and respond to unpredictable and frequent environmental changes throughout the activity. Closed-skilled types of physical activity, such as swimming, are predictable and self-directed. However, the benefits of cognitive function in these two types of physical activities to older adults are unknown. This study examined the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
2
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 77 publications
1
29
2
2
Order By: Relevance
“…The brain-derived neurotrophic factor (BDNF) promotes neurogenesis and neuroplasticity [11], while the insulin-like growth factor (IGF-1) confers neuroprotection and neural repair [12]. Therefore, exercise supports processes that improve cognitive functions and mental wellbeing, which are essential for the matured brain [13]. Several studies described individually the impact of diet and exercise on mental wellbeing; however, the integrated associations between dietary patterns, dietary practices and exercise frequency on mental distress in mature adults have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The brain-derived neurotrophic factor (BDNF) promotes neurogenesis and neuroplasticity [11], while the insulin-like growth factor (IGF-1) confers neuroprotection and neural repair [12]. Therefore, exercise supports processes that improve cognitive functions and mental wellbeing, which are essential for the matured brain [13]. Several studies described individually the impact of diet and exercise on mental wellbeing; however, the integrated associations between dietary patterns, dietary practices and exercise frequency on mental distress in mature adults have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The study found higher physical fitness in older persons to be associated with higher global cognitive function scores, memory, executive function, and motor abilities [ 25 ]. Several recent studies have also shown that physical activities promotes cognitive vitality [ 26 , 27 ], Daimiel and colleagues argued based on their investigation involving 6874 participants in Spain, that physical fitness, but not physical activity, was associated with a higher cognitive function [ 28 ]. They found that physical fitness correlated with higher MMSE language domain score and total score [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Swimming reduces myocardial oxygen demand, making the heart more efficient 6 , and reduces hypertension rates and improves blood lipid profiles in middle-aged women 7,8 . Cognitively 9 , elderly swimmers score higher on executive functioning tests and complete cognitive tasks faster than nonswimmers 10,11 .…”
mentioning
confidence: 91%